Suppression of peroxisomal lipid β-oxidation enzymes by TNF-α - Beier, Konstantin; Völkl, Alfred; Fahimi, H. Dariush (FEBS letters, 1992)
TNF-α is a potent cytokine which induces marked hyperlipidemia. Because of the important role of peroxisomes in lipid metabolism we investigated the effects of human recombinant TNF-α upon rat liver peroxisomal enzymes. Sixteen hours after the administration of a single dose of 25 μg of TNF-α to male rats the activity of peroxisomal fatty acyl-CoA oxidase was reduced by 50%. This was confirmed also by immunoblotting and by quantitative immunoelectron microscopy which in addition revealed substantial reduction of the trifunctional protein (hydratase—dehydrogenase—isomerase) in peroxisomes. These observations suggest that the suppression of peroxisomal β-oxidation may contribute to the perturbation of the lipid metabolism induced by TNF-α.